Leaf Polyphenolic Profile as a Determinant of Croatian Native Grapevine Varieties’ Susceptibility to Plasmopara viticola - Štambuk, Petra; Šikuten, Iva; Karoglan Kontić, Jasminka; Maletić, Edi; Preiner, Darko; Tomaz, Ivana (Frontiers in Plant Science, 2022)
Since grapevine is highly susceptible to various pathogens, enormous amounts of pesticides are applied each season to achieve profitable production. One of the most destructive grapevine diseases is downy mildew, and their interaction has been in the spotlight for more than a decade. When it comes to a metabolome level, phenolic compounds are relevant to investigate due to their involvement in the plant immune system and known antifungal properties. Croatian grapevine germplasm is highly heterogeneous due to its long history of cultivation in diversified geographical regions. Since it has been found that native varieties react differently to the infection of Plasmopara viticola, the intention of this study is to define if the chemical background of the leaves, i.e., polyphenolic composition, is responsible for these dissimilarities. Therefore, the leaves of 17 genotypes, among which 14 were native and 3 were controls, were analyzed using high-performance liquid chromatography (HPLC) in four terms: before inoculation and 24, 48, and 96 h post inoculation (hpi). During this early phase, significant differences were found neither between the terms nor between the non-inoculated and inoculated samples, except for resveratrol-3-O-glucoside. By applying principal component analysis (PCA) using initial leaf polyphenolic composition, varieties of V. vinifera were clearly separated into three different groups corresponding to their International Organization of Vine and Wine (OIV) classes of susceptibility to P. viticola. Results obtained in this research suggest that the initial constitutive polyphenolic composition of the cultivar leaves has a crucial influence on their susceptibility to P. viticola, and this finding can be used to improve the success of grapevine breeding programs toward downy mildew resistance.